Sacralised Land: The Symbolic Dimension of Land in the Israeli-Palestinian Conflict - Valentina Bartolucci (Scienza & Politica)
Land is a central element to the war imagination. Terrible wars and bloody massacres have been waged in its name. This paper aims to analyse its symbolic significance. Although it strongly influences the likelihood and intensity of war, it remains understudied and underestimated. Drawing on 'the theory of sacralisation' and bridging a 'symbolic politics' framework with a conflict resolution perspective, the article shows the importance of recognising the symbolic significance of land in trying to overcome the 'absolutisms' that have kept us trapped for so long and prevented us from imagining 'other worlds' of conflict resolution without resorting to war. The article proceeds as follows: after introducing the relevance of the symbolic significance of land, it presents a discussion of the 'sacralisation of land' through an analysis of the Zionist aspiration for a Jewish state.